Assessment of Knowledge, Attitude, and Practice of Iranian Nurses towards Toothbrush Maintenance and Use - Mohammad Nazarianpirdosti; Maryam Janatolmakan; Bahare Andayeshgar; Alireza khatony (Nursing Research and Practice)
Background. Since nurses are considered a role model in society, they should have sufficient knowledge, attitude, and practice in the field of oral hygiene. This study was aimed to assess the nurses’ knowledge, practice, and attitude towards toothbrush maintenance and use. Methods. In this cross-sectional study, 325 nurses working in hospitals affiliated to Kermanshah University of Medical Sciences were randomly recruited. Data collection tools included a demographic information form and a researcher-made questionnaire on knowledge, attitude, and practice regarding toothbrush maintenance and use. Data were analyzed by SPSS software using descriptive and inferential statistics (Mann–Whitney U and Kruskal–Wallis H). Results. The mean scores of nurses’ knowledge, attitude, and practice were 59.2 ± 16.4, 64.2 ± 20.6, and 51.4 ± 17.0 out of 100, respectively. There was no statistically significant relation between nurses’ knowledge, attitude, and practice and their gender, age, level of education, and work experience. Conclusions. Nurses had moderate knowledge, attitude, and practice regarding toothbrush maintenance and use, which is not very desirable given their role model. Therefore, training courses are recommended to be held to increase the nurses’ knowledge, attitude, and practice regarding toothbrush maintenance and use.